Allicin Alleviates Inflammation of Trinitrobenzenesulfonic Acid-Induced Rats and Suppresses P38 and JNK Pathways in Caco-2 Cells - Chen Li; Weijian Lun; Xinmei Zhao; Shan Lei; Yandong Guo; Jiayi Ma; Fachao Zhi (Hindawi Limited, 2015)
Background. Allicin has anti-inflammatory, antioxidative and proapoptotic properties. Aims. To evaluate the effects and investigate the mechanism of allicin on trinitrobenzenesulfonic acid-induced colitis, specifically with mesalazine or sulfasalazine. Methods. 80 rats were divided equally into 8 groups: control; trinitrobenzenesulfonic acid; allicin prevention; allicin; mesalazine; sulfasalazine; allicin + sulfasalazine, and mesalazine + allicin. Systemic and colonic inflammation parameters were analysed. In addition, protein and culture medium of Caco-2 cells treated with various concentrations of IL-1β or allicin were collected for investigation of IL-8, NF-κB p65 P38, ERK, and JNK. One-way ANOVA and Kruskal-Wallis H test were used for parametric and nonparametric tests, respectively. Results. Allicin reduced the body weight loss of trinitrobenzenesulfonic acid-induced rats, histological score, serum TNF-α and IL-1β levels, and colon IL-1β mRNA level and induced serum IL-4 level, particularly in combination with mesalazine. In addition, 1 ng/mL IL-1β stimulated the P38, ERK, and JNK pathways, whereas pretreatment with allicin depressed this phenomenon, except for the ERK pathway. Conclusions. The inflammation induced by trinitrobenzenesulfonic acid is mitigated significantly by allicin treatment, particularly combined with mesalazine. Allicin inhibits the P38 and JNK pathways and the expression of NF-κB which explained the potential anti-inflammatory mechanisms of allicin.